2016
DOI: 10.1016/j.electacta.2016.10.109
|View full text |Cite
|
Sign up to set email alerts
|

Supercapacitors based on two dimensional VO 2 nanosheet electrodes in organic gel electrolyte

Abstract: (a) CVs of solid state device measured at different angles (inset shows the schematic for the measurement of the bending angles and the optical image of the flexible supercapacitor device). (b) Optical images displaying lighting up of an LED using three flexible supercapacitors connected in series. Highlights  Synthesis of 2D VO2 nanosheets by hydrothermal reduction of V2O5 nanopowder.  A specific capacitance of 405 F g-1 in organic electrolyte at 1 A g-1.  An energy density of 46 Wh kg-1 at 1 Ag-1 for VO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…Due to the preservation of good properties during loading and unloading processes, relatively easy transfer of lithium ions, several degrees of oxidation (V 3+ , V 4+ , V 5+ ), ease of synthesis and lack of toxicity, they are a good basis for working with lithium-ion cells. They also provide good cycling stability [6][7][8][9]. Vanadium oxides are regularly used in research works around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the preservation of good properties during loading and unloading processes, relatively easy transfer of lithium ions, several degrees of oxidation (V 3+ , V 4+ , V 5+ ), ease of synthesis and lack of toxicity, they are a good basis for working with lithium-ion cells. They also provide good cycling stability [6][7][8][9]. Vanadium oxides are regularly used in research works around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al prepared 3D graphene/VO 2 nanobelt for high-performance supercapacitors by hydrothermal strategy which exhibited a specific capacitance of 191 F g -1 at a current density of 1 A g -1 in 0.5 M K 2 SO 4 aqueous solution [1]. Rakhi et al reported VO 2 nanosheets electrodes in organic gel electrolyte for supercapacitor applications by hydrothermal method and the electrodes exhibited a specific capacitance of 405 F g -1 at a current density of 1 Ag -1 [18]. Xiao et al reported the composite of metastable vanadium dioxide [VO 2 (B)] nanobelts on reduced graphene oxide (RGO) layers by one-step hydrothermal process which exhibited a specific capacitance of 290.4 F g -1 at a current density of 0.2 A g -1 in 1 M Na 2 SO 4 aqueous solution [19].…”
Section: Introductionmentioning
confidence: 99%
“…Liming et al prepared VO 2 /ordered mesoporous carbon (CMK-3) composites for hybrid capacitors by solid-state reaction process which exhibited a specific capacitance of 131 F g -1 in 1 M KNO 3 aqueous solution [20]. In brief, previously reported VO 2 based electrodes are mainly composites which exhibited specific capacitance values in the range of about 130 to 430 F g -1 [10,14,18,20,21], and were not evaluated in 6 M KOH as the electrolyte. In fact, to the best of our knowledge, no report exist on the electrochemical performance of VO 2 electrode in 6 M KOH aqueous electrolyte until the present.…”
Section: Introductionmentioning
confidence: 99%
“…Supercapacitors consisting of VO 2 /GO nanobelts possessed a capacitane value of 426 F/g at 1 A/g in the potential range of − 0.6 to 0.6 V [ 29 ]. VO 2 nanoflake arrays deposited on a carbon matrix showed capacitance values of 485 F/g at 2 A/g [ 34 ]. VO 2 /CNT nanocomposites synthesized by atomic layer deposition exhibited a capacitance up to 1550 F/g [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In pure VO 2 nanocrystals, insufficient control of its microstructure at nanoscale typically existed and thus leaded to unsatisfied capacitance and cycle performance. VO 2 nanosheet-based electrode materials obtained a capacitance of 150 F/g at 1 A/g [ 34 ]. Pure nanoporous VO 2 electrodes only exhibited capacitance values of 76 F/g at 1 A/g [ 33 ].…”
Section: Introductionmentioning
confidence: 99%